Ответы и объяснения

2012-12-26T23:49:08+04:00

По формуле приведения:

3*sin2x=1

3(2sinx*cosx)=1

6sinx*cosx=1

6sinx*cosx=cos^2x+sin^2x

-sin^2x+6sinx*cosx-cos^2x=0

Разделим на cos^2x не равный 0, получи ур.

-tgx+6tgx-1=0

tgx=y

-y+6y-1=0

D=\sqrt{32}

X(1)=-6+\sqrt{32}/2

X(2)=-6-\sqrt{32}/2

  • fuflunce
  • почетный грамотей
2012-12-26T23:52:52+04:00

3*cos(2*x+pi/4)=1

cos(2*x+pi/4)=1/3

2*x+pi/4 = +-arccos(1/3) + 2pik

2x = +-arccos(1/3) + 2pik - pi/4

x = +-0,5arccos(1/3) + pik - pi/8